4CPS-095 Infusion audit in haematology: importance of evaluation and optimisation of professional practices. Issue 1 (23rd March 2023) - Le Guen, C; Ammor, W; Clouet, J; Sellal, KO; Feldman, D; Fronteau, C; Lindenberg, F
Abstract : Background and Importance: Intravenous administration is the source of numerous identified risks requiring periodic evaluation of professional practices. In February 2022, an observational audit in the haematology unit was carried out in order to optimise the infusion setups. Aim and Objectives: The objective of this audit is to evaluate the professional practices of the nursing team and thus to implement permanent corrective actions. Material and Methods: An evaluation grid based on the good infusion practices defined by the 'Observatoire du Médicament, des Dispositifs médicaux et de l'Innovation Thérapeutique' Centre was updated and validated by a multidisciplinary group. In February 2022, two pharmacy interns observed 62 drugs administered by analysing the prescriptions of all hospitalised patients in the unit. Results: Regarding the infusion configuration, only 90% of the peripheral infusion line were closed using an adapted plug. No misuse was observed on the administration of parenteral nutrition. Regarding flow rate problems, only one infusion configuration exhibits an infusion drip chamber filled beyond the maximum limit. Interestingly, during a flow-sensitive drug infusion and contrary to guidelines, absence of non-return valve was observed in 9% of the infusion configuration. A potential risk of drug incompatibility has also been identified with the current perfusion set-up. Conclusion and Relevance: The results of this audit appear to be very positive. The haematology unit, whose nursing team is aware of the risks associated with the administration of chemotherapy, is a unit accustomed to the availability of pharmacists. This audit allowed us to observe some errors during infusion practice: inadequate programmed flow rate, absence of plugs and absence of non-return valve during flow-sensitive drugs infusion. In order to improve infusion practice, a new standardised infusion set-up will be proposed to the unit including non-return valves. This set-up should make it possible to reduce the risks, particularly those related to flow rate and incompatibilities. However, this change in practice will require support for the teams and a new audit to evaluate the impact of this work. References and/or Acknowledgements: Conflict of Interest: No conflict of interest